Optimizing Quantum Key Distribution Protocols using Decoy State Techniques and Experimental Validation - Ali, Sellami; Djaouida, Benlahcene (Engineering, Technology & Applied Science Research, 2024)
This paper simulated the operation of vacuum state and single decoy state protocols in the BB84 and SARG04 QKD schemes by utilizing the features of the commercial ID-3000 QKD system. Numerical modeling identified an optimal signal-to-decoy state ratio of 0.95:0.05 and an intensity of μ=0.85 for the signal state and ν1=0.05 for the decoy state, ensuring the highest key generation rate and a secure distance of up to 50 km. These protocols were validated experimentally over various transmission distances with standard telecom fiber, using the ID-3000 QKD system in a conventional bi-directional plug-and-play setup. Simulations predicted secure key rates of 1.2 × 10 5 bits/s for SARG04 and 8.5 × 104 bits/s for BB84 at 10 km, with secure distances of 45 km and 35 km, respectively. The experimental results confirmed these predictions, showing a 30% higher key rate and 20% longer secure distance compared to non-decoy methods. The SARG04 protocol surpassed BB84 in key rate and secure distance, highlighting the two-photon component’s role in key generation. This study concludes that the decoy-state method significantly enhances key generation rates and secure distances, optimizing QKD protocols for secure quantum communication.